SIGNIFIKANSI LITERASI INFORMASI (INFORMATION LITERACY) DALAM DUNIA PENDIDIKAN DI ERA GLOBAL - Aris Nurohman (Jurnal Kependidikan, 2014)
The globalization era has imperceptible impacts on all sectors, one of which is education. The rapid changes in the era lead to a significant increase in the environmental community, which are driven by transculturation and the development of information and communication technology and the booming of information and knowledge. As a result, the world of education has gone in such a dynamic way as the era of globalization. The development of knowledge, experiences, innovations and a variety of things related to the globalization of education make up what is called the information resources. The information literacy has been needed by the education community, so that education will be able to compete on a global level. The information literacy will be proper in complying with the development. This is the actual demand for the academic community. Moreover, the information literacy will meet the demands of development faster. This is actually a request for the academic community.